Osteoarticular Complications of Sickle Cell Disease in Bukavu: A Retrospective Multicenter Cross‐Sectional Study - Rodrigue Mwenibamba Mupenda; Alexandre Nechi Nakashenyi; Daniel Safari Nteranya; Viviane Feza Bianga Viviane; Fernand Manga Opondjo; Sarah Mbula Mulasi; Didier Mbilizi Kasilembo; Christian Bisimwa Wabene; Eugene Munyantwari Akomu; Uwonda Akinja; Jean Marrie Vianney Tshimbila Kabangu (Health Science Reports)
ABSTRACT Background and Aim This study aimed to investigate the epidemiological, clinical, and therapeutic aspects of osteoarticular complications in patients with sickle cell disease in Bukavu. Methods We conducted a multicenter cross‐sectional study over 5 years, focusing on 31 patients with sickle cell disease who were admitted for osteoarticular complications in Bukavu. Data were collected from medical records and analyzed with the Statistical Package for Social Science 26 (IBM, SPSS 26). Results We recorded 31 (6.07%) sickle cell patients with osteoarticular complications, with a mean age of 10.5 ± 5.6 years (extremes: 2–30 years). Pain, fever, and functional impotence were the most frequent reasons for consultation with 9 (29.03%) patients. Septic arthritis was the most common complication in 10 (32.26%), followed by osteonecrosis of the femoral head in 8 (25.81%), chronic osteomyelitis in 7 (22.58%) cases, and acute osteomyelitis in 4 (12.70%) patients. The femur was the most affected bone. Articular complications predominantly impacted larger joints, with the knee joint experiencing the highest rate of damage, occurring in 38.71% of cases. Treatment, including medical and surgical methods, was provided in 16 cases (51.6%). Complete healing without residual effects was achieved in 22 patients (70.96%). Conclusion The osteoarticular complications of sickle cell disease are frequent in the city of Bukavu, and regular monitoring and early consultation would enable early diagnosis and management.